Implementasi Kemandirian Anak Usia 3-5 tahun di TK Islam Kauman Kota Pekalongan - Ni'matul Ulya; Pedvin Ratna Meikawati; Putri Andanawarih (LPPM Akbid Harapan Ibu Pekalongan, 2020)
Children aged 3-5 years are considered as a child's age to learn skills to fulfill their desires independently. Children aged 3-5 years must be able to do activities, such as eating and drinking by themselves, bathing and dressing themselves, combing hair, walking, running, and taking things that they need themselves. Family factors are very influential on the formation of independence in a child. Based on the results of interviews with 10 mothers (guardians of students) in one private kindergarten in Pekalongan City, it was found that 2 mothers said that their children had never played outside the home, rarely socialized and were ashamed. A total of 6 mothers said their children could not wear their own clothes and sometimes their parents still fed food and 2 mothers said their children were very spoiled, did not want to clean up the game. Community service activities conducted at the Kauman Islamic Kindergarten are aimed at providing skills to children aged 3-5 years to be able to carry out their daily activities independently. The method used in this activity is demonstration and hands-on practice. The results obtained as many as 48 students were able to wear clothes independently, 39 students were able to fold their own clothes, 26 students were able to button their own clothes, and 27 students were wearing socks independently.